Smart alloys for a future fusion power plant: First studies under stationary plasma load and in accidental conditions. (August 2017) - Litnovsky, A.; Wegener, T.; Klein, F.; Linsmeier, Ch.; Rasinski, M.; Kreter, A.; Unterberg, B.; Vogel, M.; Kraus, S.; Breuer, U.; Garcia-Rosales, C.; Calvo, A.; et al.
Highlights: Advanced tungsten-based smart alloys are being developed for future fusion power plant Smart alloys will be used as plasma-facing components and as a passive safety measure in case of accident. First direct comparative test of smart alloy and pure tungsten under identical plasma and accidental conditions was made. Smart alloys featured similar sputtering as that of pure tungsten during plasma exposure. Smart alloys demonstrate the 3-fold suppression of oxidation during the simulated accident as compared to pure tungsten. Abstract: In case of an accident in the future fusion power plant like DEMO, the loss-of-coolant may happen simultaneously with air ingress into the vacuum vessel. The radioactive tungsten and its isotopes from the first wall may become oxidized and vaporized into the environment. The so-called "smart" alloys are under development to suppress the mobilization of oxidized tungsten. Smart alloys are aimed at adjusting their properties to environment. During regular operation, the preferential sputtering of alloying elements by plasma ions should leave almost pure tungsten surface facing the plasma. Under accidental conditions, the alloying elements in the bulk will form an oxide layer protecting tungsten from mobilization. The first direct comparative test of pure tungsten and smart alloys under identical plasma conditions was performed. Tungsten–chromium–titanium alloys were exposed simultaneously with tungsten samples to stationary deuterium plasma in linear plasma device PSI-2. The ion energy and the temperature of samples corresponded well the conditions at the first wall in DEMO. The accumulated fluence was 1.3 × 10 26 ion/m 2 . The weight loss of pure tungsten samples after exposure was Δ m W = 1000–1150 µg. The measured weight loss of sputtered smart alloy sample Δ m SA = 1240µg corresponds very well to that of pure tungsten providing experimental evidence of good resistance of smart alloys to plasma sputtering. Plasma exposure was followed by the oxidation of alloys at 1000 °C accomplishing the first test of these new materials both in a plasma environment and under accidental conditions. Compared to pure tungsten, smart alloys featured the 3-fold suppression of oxidation. Plasma exposure did not affect the oxidation resistance of smart alloys. At the same time, the self-passivation of the protective layer did not occur, calling for further optimization of alloys.